Effect of the Number of Dipping Cycles for a Cadmium Oxide Film Prepared by SILAR Method - AL-Tememee, Nathera Abass Ali; Jawad, Fahmi Kadhum; Jabor, Ashwaq A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
The thin films of cadmium oxide (CdO) were deposited using the SILAR (Successive ionic layer absorption and reaction) method at various deposition cycles. CdO thin films were made on glass substrates at a temperature of  95°C, using a cadmium acetate source material and an ammonium hydroxide solution. One of the main criteria that impact the quality of thin films is the number of deposition cycles. The size of the crystals decreases with the increase in the number of cycles from 33.7 nm at the immersion cycle 10 to 22.7 nm at the immersion cycle 20, as shown by the X-ray diffraction results. The optical band gap energy of the films reduces as the number of deposition cycles increases, while the transmittance of the Cadmium oxide film increases as the dipping cycle increases. FTIR analytics of the sample showed that the transmittance increases with the immersion cycles. The thickness of the sample measured by the Michelson method increases with the increase in sedimentation.